Cuban publications about cardio-pulmonary-cerebral resuscitation: a bibliometric approach from 1998 to 2018 - Jayce Díaz Díaz; Arelys Falcón Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Introduction: multiple researches have been developed along the years about cardio-pulmonary (CPR); new evidences appear and scientific articles are published regularly which show its development. Objective: to characterize scientific publications about CPR in Cuba. Methods: descriptive bibliometric, retrospective study done from January 1998 to November 2018. All Cuban publications indexed to Scientific Electronic Library Online (Scielo) were reviewed. Editorials and letters to the editor were not included. It was designed a registration folder in Microsoft Office Excel 2010, in which the information about the articles was organized for their identification, counting and analysis of the bibliometric indicators. Results: from the 83 articles indexed in Scielo, only 24 had the requirements to be included, there was predominance of original articles with 58, 3%, followed by reviews. Regarding the number of authors per article the category 3 to 6 authors was the most frequent, with 5 articles. Conclusion: scientific production related to cardio-pulmonary-cerebral resuscitation has been unstable and poor. The periods of greater scientific production were 2003 and 2017. There is a predominance of original articles followed by reviews.